Adherence to Antiretroviral Therapy and Influencing Factors among People Living with HIV: A Literature Review - Ni Wayan Deani; I Gede Putu Darma Suyasa; Putra, I Nyoman Arya Maha; Kadek Sriasih (Babali Nursing Research, 2026)
Introduction: Antiretroviral therapy is the main treatment for HIV/AIDS, requiring lifelong medication to suppress the virus, prevent complications, and improve the patient's quality of life. However, adherence to ARV medication remains low, influenced by factors such as self-efficacy, social support, spirituality, depression, and various clinical and psychosocial conditions. This study aimed to review studies on ARV medication adherence and its factors among HIV patients. Methods: This literature review explored studies on ARV medication adherence among HIV patients. Searches were conducted in Google Scholar, ScienceDirect, PubMed, Scopus, Web of Science, and CINAHL using keywords related to HIV, ARV adherence, self-efficacy, non-family caregivers, spirituality, and depression. The inclusion criteria consisted of original research articles published between 2020 and 2025 in English or Indonesian that examined factors influencing ARV adherence. Exclusion criteria included abstract-only papers, blogs, news articles, and review papers. Study quality was assessed using the JBI Critical Appraisal Checklist, and risk of bias was evaluated based on sampling methods, measurement tools, confounding factors, and data completeness. Findings were synthesized narratively. Results: A total of 1,653 publications were identified, and 15 studies met all criteria for inclusion. Overall, ARV adherence among HIV patients remained below the national 95-95-95 target. Key influencing factors were self-efficacy, social support (including non-family caregivers), spirituality, and depression, indicating that adherence is shaped by multiple interacting psychosocial and clinical dimensions. Conclusion: Strengthening self-efficacy, enhancing spiritual well-being, and reducing depressive symptoms may improve ARV medication adherence. Future research should explore integrated psychosocial–spiritual interventions and employ longitudinal or mixed-methods designs to understand better the causal pathways affecting ARV adherence.